Bioactive compounds, antioxidant activity and fruit quality evaluation of eleven blood orange cultivars. (19th November 2021) - Legua, Pilar; Modica, Giulia; Porras, Ignacio; Conesa, Agustín; Continella, Alberto
Abstract: BACKGROUND: Blood oranges are grown increasingly in Europe for fresh consumption because of their special taste and excellent nutraceutical properties that confer the status of a functional food. The health benefits are associated with the range of additional bioactive compounds that they contain with respect to blonde oranges. RESULTS: We analysed the physicochemical properties and the levels of organic acids, sugars and antioxidants in 11 blood orange cultivars representing the most representative cultivars of blood oranges widespread in the Mediterranean basin. In particular, we examined the levels of phenols, flavonoids and anthocyanins present in these cultivars at harvest maturity. The physicochemical, antioxidant and colour properties differ significantly among these cultivars. The deepest red peel and juice was found in Sanguinelli, followed by Tarocco Rosso and Moro. High‐performance liquid chromatography with refractive index detector analysis revealed sucrose as the main sugar in all these cultivars, followed by fructose and glucose. Citric acid was the dominant organic acid, followed by malic acid and ascorbic acid. Moro showed the greatest levels of antioxidant activity. Regarding the phenolic composition, we found p ‐coumaric acid to be the main hydroxycinnamic acid in all cultivars, with maximum amounts in Moro and Sanguinelli. The highest amounts of cyanidin‐3‐ O ‐glucoside and cyanidin‐3‐(6′′‐malonyl)‐glucoside were found in Moro, for which the juice was of the deepest red colour. CONCLUSION: The phenolic composition and antioxidant activity of the 11 cultivars was assessed. The results showed that Moro was the cultivar with the highest content of polyphenols and levels of antioxidant activity, followed by Sanguinelli. © 2021 The Authors. Journal of The Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.